السياسة الشرعية في أداء الأمانات - مبروكة درم; عائشة حاجي; د/عباس حفصي (جامعة عمار ثليجي الاغواط, 2023)
الممخص شممت المقدمة كممة عف السياسة الشرعية كأداء الأمانات بنكعييا خاصة الكلاية، كتظير أىميتيا في ككنيا تقك عمى رعاية مصالح العباد، ك مف أى أىدافيا ضركرة تنصيب كلي في الدكلة ، كطرحنا الإشكاؿ الذم يعالجو المكضكع، ث خطة البحث، كللإجابة عمى ذلؾ الإشكاؿ قسمنا المكضكع إلى فصميف ذكرنا فييما الآتي: الفصؿ الأكؿ: اشتمؿ لمحة تاريخية عف السياسة الشرعية كأى تعريفات الفقياء ليا، كما كرد في السنة مف ذكر ليا، كبينا أىميتيا في تنظي الدكلة مف خلاؿ تنفيذىا للأحكا الشرعية عمى الرعية، كذكرنا أنكاعيا مف حيث العدؿ كالظم كالعمك كالخصكص، كعرفنا أداء الأمانة بأنيا ىي القدرة عمى التصرؼ في ما يؤتمف عميو مع رد المستكدع إلى مكدعو، كبينا أنكاعيا بشكؿ عا كفصمنا في الكلايات ككؿ ما يمد ليا بصمة مف مصطمحات، كتعرؼ الكلاية بأنيا: قدرة الشخص عمى التصرؼ عمى نفسو كمالو كعمى غيره. أما الفصؿ الثاني: بينا حك الكلاية بالأدلة الشرعية، كشرحنا حد تصرؼ كؿ كلي فيما يجب عميو، كغايتيا رعاية شؤكف الأمة في ديني كدنياى، كأف الكلي لتكليو أمكر الأمة يجب عميو أف يستكفي كؿ الشركط التي قد فصمنا فييا، كأنيا تقك عمى ركنيف ىما: أف يككف الكلي قكيا كأمينا ليتمكف مف حك دكلة الإسلا بالعدؿ، كتطرقنا إلى أنكاع الكلاية بالتفصيؿ فالعامة منيا: كلاية كؿ مف الإما كالقاضي كالحج، ككذلؾ الخاصة: كلاية )القضاء كالمظال كالحسبة كالماؿ كالصدقات كالنفس كالمصالح(، كبينا الفرؽ بيف نكعي الكلاية. ك خاتمة شممت النتائج المتكصؿ إلييا بإيجاز. الكممات المفتاحية: السياسة الشرعية كأداء الأمانة كالكلاية. الملخص Abstract In the introduction, we mentioned an overview about the legal policy and the performance of trusts of both types, especially the mandate in which its importance appears in the way of taking care of the interests of the people, and one of its most important goals is the need to install a guardian in the state, and we raised the problems that the topic deals with, then the research plan, and in order to answer this problematic, we divided the topic into two chapters in which we mentioned the following: The first chapter includes a historical overview of the legal policy and the most important definitions of the jurists about, in addition to its mention in the Sunnah. To dispose of what is entrusted to it with the return of the warehouse to its depositor, then we explained its types in general and we separated in the states and everything that provides them with a connection of terms, and the state can be defined as: the ability of a person to dispose of himself, his money and others. While in the second chapter, We clarified the ruling on guardianship with legal evidence, and we explained the limit of each guardian’s disposal in what he is obliged to do, and its purpose is to take care of the affairs of the nation in their religious and worldly affairs, and that the guardian, in order to take charge of the affairs of the nation, must fulfill all the conditions that we have discussed, and that it is based on two pillars: that The guardian is strong and trustworthy to be able to rule the Islamic state with justice moreover, we have touched on the types of guardianship in detail. Finally, the study contained a conclusion that briefly included the findings. Keywords: Sharia policy, performance of trust, and guardianship.